Rising Into Relevance: A Rare Case of Pyelonephritis in an Immunosuppressed Patient With Exposure to Sourdough Starter - Alissa Mingo BS; Drew Stone MD; Andrew D. Schreiner MD, MSCR; Richard Lueking MD (Journal of Investigative Medicine High Impact Case Reports)
Saccharomyces cerevisiae , commonly known as Baker’s yeast, has been used in breadmaking, winemaking, and beer brewing for centuries. Although not generally regarded as pathogenic, rare cases of invasive infections have occurred in patients predisposed by critical illness, immunosuppression, or prolonged antibiotic use. Using data collected from the electronic medical record and personal interactions with the patient, we present a case of complicated S cerevisiae urinary tract infection (UTI). We searched terms (and permutations of terms) including Saccharomyces cerevisiae , Baker’s or Brewer’s yeast, and urinary tract infection using PubMed to identify previously published evidence of invasive S cerevisiae infections. Our patient is a 30-year-old woman with a history of rheumatoid arthritis on methotrexate, and previous admission for Candida glabrata UTI requiring intravenous antifungal therapies, who presented to her gynecologist with complaints of vaginitis and flank pain. Vaginal and urine cultures grew S cerevisiae , and the patient was diagnosed with pyelonephritis and admitted for treatment. A further review of the patient’s history revealed daily exposure to S cerevisiae through baking sourdough bread. She was treated with 7 days of IV amphotericin deoxycholate and discharged on a 6-month course of suppressive oteseconazole for vulvovaginitis suppression. Saccharomyces cerevisiae is an exceedingly rare cause of invasive fungal UTI, with our literature review identifying only a few case reports of associated UTI and fungemia, all related to probiotic use. Our case emphasizes the importance of careful history taking and early diagnostic cultures in those at risk of invasive fungal infections.